2020
DOI: 10.1161/hypertensionaha.119.14308
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 Mediates the Systemic and Renal Hemodynamic Effects of GPR81 Activation

Abstract: Endothelin-1 mediates the systemic and renal hemodynamic effects of GPR81 activation', Hypertension. G PR81 (G-protein-coupled receptor 81), GPR109a, and GPR109b form the hydroxycarboxylic acid receptor subfamily. 1 Encoded by the HCAR1 gene, GPR81 is predominantly expressed in brown and white adipose tissue. 2 L-lactate is the endogenous ligand with an EC 50 of ≈5 mmol/L. 3 Lactate, formed from pyruvate during anaerobic glycolysis, has a physiological plasma concentration of 0.5 to 2 mmol/L, rising from 10 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…Pericyte-mediated constriction of renal capillaries may reflect reduced Ca 2+ pumping in ischemia, raising [Ca 2+ ] i which activates contraction, as for CNS pericytes (Hall et al, 2014). Constriction may also partly reflect a release of angiotensin II (Allred et al, 2000; Boer et al, 1997; da Silveira et al, 2010; Miyata et al, 1999; Sanchez-Pozos et al, 2012; Zhang et al, 2004) and endothelin 1(Afyouni et al, 2015; Jones et al, 2020; Sanchez-Pozos et al, 2012) which raise [Ca 2+ ] i and Rho kinase activity (Lee et al, 2014; Shimokawa & Rashid, 2007), since we found that blocking endothelin 1 receptors and, to a lesser extent, angiotensin II receptors improved post-ischemic renal blood flow. Consistent with this, it has been demonstrated that vasoconstricting endothelin-A (Crawford et al, 2012; Wendel et al, 2006) and the angiotensin II type 1 (AT1) (Crawford et al, 2012; Miyata et al, 1999; Terada et al, 1993) receptors are located on pericytes along the descending vasa recta and regulate contractility at pericyte sites (Crawford et al, 2012).…”
Section: Discussionmentioning
confidence: 49%
“…Pericyte-mediated constriction of renal capillaries may reflect reduced Ca 2+ pumping in ischemia, raising [Ca 2+ ] i which activates contraction, as for CNS pericytes (Hall et al, 2014). Constriction may also partly reflect a release of angiotensin II (Allred et al, 2000; Boer et al, 1997; da Silveira et al, 2010; Miyata et al, 1999; Sanchez-Pozos et al, 2012; Zhang et al, 2004) and endothelin 1(Afyouni et al, 2015; Jones et al, 2020; Sanchez-Pozos et al, 2012) which raise [Ca 2+ ] i and Rho kinase activity (Lee et al, 2014; Shimokawa & Rashid, 2007), since we found that blocking endothelin 1 receptors and, to a lesser extent, angiotensin II receptors improved post-ischemic renal blood flow. Consistent with this, it has been demonstrated that vasoconstricting endothelin-A (Crawford et al, 2012; Wendel et al, 2006) and the angiotensin II type 1 (AT1) (Crawford et al, 2012; Miyata et al, 1999; Terada et al, 1993) receptors are located on pericytes along the descending vasa recta and regulate contractility at pericyte sites (Crawford et al, 2012).…”
Section: Discussionmentioning
confidence: 49%
“…Likewise, treatment with the GPR81 agonist, 3,5-dihydroxybenzoic acid, ameliorated DSS-induced colitis and reduced inflammationassociated injury in the colon (30). Other studies have shown that pharmacological activation of the GPR81 pathway suppresses inflammation and inflammation-associated tissue injury in other immune cell-mediated inflammatory diseases (31,(141)(142)(143). Further studies in understanding the lactate signaling networks in a context-dependent manner will aid in the development of effective treatments for many inflammatory diseases.…”
Section: Targeting Lactate-gpr81/gpr132 Signalingmentioning
confidence: 97%
“…Based on the presence of ET‐1 and GPR81 in renal endothelial cells, and the fact that ET‐1 production is stimulated by low cAMP levels, both pathways may likely cooperate via the G i protein‐dependent lowering of cAMP (Jones et al, 2020; Wallenius et al, 2017). Additionally, Jones et al reported that GPR81 stimulation reduced the glomerular filtration rate, renal artery blood flow, and intrarenal tissue perfusion, simultaneously with higher blood pressure in a mouse model.…”
Section: Influence Of Gpr81 On Neovascularization/hemodynamics In Dia...mentioning
confidence: 99%